Pemberdayaan Masyarakat Pada Home Industry Sirup Markisa di Desa Sukamantri Kabupaten Bogor - Nadia Inayah; Muhtadi (Politeknik Pembangunan Pertanian Bogor, 2022)
Community empowerment activities are carried out at the passion fruit syrup home industry located in Sukamantri Village, Bogor Regency. The purpose of this empowerment activity is to help the owner so that his business increases and the community becomes more productive by carrying out empowerment activities. There are 4 activities in the empowerment of passion fruit syrup, namely: 1) Seeing potential problems, 2) Planning activities, 3) Carrying out empowerment activities, 4) Program evaluation, 5) Analyzing supporting and inhibiting factors. The method used is a qualitative approach, with interviews, observations, and documentation, and uses triangulation techniques. There are 5 participants in this activity, 3 housewives, and 2 residents who have not worked (unemployed). The results of this study are to see that the potential in this village has a fairly large plantation area of 1,760,000 hectares and has cool air and high rainfall which is very suitable for cultivating passion fruit, the intended location is the passion fruit syrup home industry owned one of the farmers who uses his land to cultivate passion fruit into passion fruit syrup and can open job vacancies for the community. Planning and implementation in this activity was carried out in 4 meetings. This activity is carried out at the home of the business owner, every Sunday, at 12.30-15.30. In the evaluation of passion fruit syrup community empowerment activities, it has shown a positive impact for participants, this can be seen from the good response of all participants in the empowerment process. The supporting factors in this activity are qualified human resources, as well as production tools and materials provided by the business owner, and the inhibiting factor in this activity is the erratic growth of passion fruit. After this activity, the participants became employees of Mr. Muiz’s passion fruit syrup home industry